Estudo da luminescência persistente em cerâmicas de Sr1-x-yMzAl(2-z)O4: Eux 2+, Dyy 3+ (M= B, Ge) e Ca1-x-y BzAl(2-z)O4: Eux 2+, Ndy 3+ sinterizadas a laser - Alves, Ylla Grasielle dos Santos (2019)
Materials that present light emission for a long period of time after ceased the excitation have received remarkable attention from the scientific community in the last decades. Among them, strontium (SrAl2O4) and calcium (CaAl2O4) aluminates, when doped with Eu2+and coded with Dy3+ and Nd3+, respectively, present persistent luminescence visible to the naked eye. In this work, it was studied the boron and germanium influence on (micro)structural and optical properties of the SrMAl2O4: Eu, Dy (M = B, Ge) and CaBAl2O4: Eu, Nd laser sintered ceramics. The powders were produced by the polymeric precursors method and the ceramics were laser sintered. For the samples characterization differential thermal analysis, thermogravimetry, X-ray diffractometry, Raman spectroscopy, scanning electron microscopy, photoluminescence and optical transmittance were used. The laser-sintered ceramics presented good homogeneity throughout the ceramic body and transmittance between 45 and 60% in a spectral range from 400 to 800 nm, with the stabilization of the monoclinic phase for both matrices. Additionally, all samples presented characteristic emission from the Eu2+, 4f65d1 → 4f7 transition and persistent luminescence up to 30 min. In SrMAl2O4: Eu, Dy caramics was confirmed the occupation of Eu2+ in the two non-equivalent strontium sites an its correlation with the luminescent decay.